Implikasi Proksi Aset, Profitabilitas dan Jenis Industri pada Islamic Social Reporting (ISR) - Debby Faras Ayu; Dodik Siswantoro (Department of Islamic Economics, IPB University, 2013)
Jakarta Islamic Index (JII) is a reference for investors to place their fund in Indonesia Stock Exchange which is in line with Islamic teaching. It has a specific requirements (screening process) which must be passed by one stock to be included in JII. Nevertheless, the screening process of JII composition is seen to have limitations because the process is merely based on the quantitative and qualitative criteria. Therefore, this research explores and analyzes the deeper aspects (Othman, et al., 2009) which is called as Islamic Social Reporting (ISR). ISR analyzes the compliance to Islamic teaching application from the company perspective. The research period is from the year of 2006 until 2008, while the research sample is taken from companies listed in the JII. This research adopts full interaction model to determine significant factors of ISR. Previous research did not apply the interaction model theory, i.e. the Difference in Difference (DiD) theory1. It can show meaningful existence of dummy variable with other proxies. The proxies used in this study are industry type, company size, and profitability. The results show that there are no differences among the industry type, while the company size affects the ISR.